Exposure to cosmetic advertisements on television and the response of the female residents of the U.P.V. Balay Madjaas. - Burao, Nieves C.
This study was conducted to find out the relationship between exposure to Cosmetic Advertisements on Television and the Response of the Female Residents of the U.P.V. Balay Madyaas., There were forty respondents which comprise the 38.46 of the total population of U.P.V. Balay Madyaas chosen for the study. The purposive sampling technique was employed in carrying out the study. This was based on certain criteria laid down by the researchers. Respondents who best fit the criteria set by the researchers were taken. In order to be qualified as respondents, one must be a female resident of the U.P.V. Madyaas and is watching television while staying at the dormitory. Findings of the study revealed that there is no significant relationship between exposure to cosmetic advertisements on television and the buying behavior of the female residents of the U.P.V. Madyaas. Except for Colour, Tawas Facial Wash, Caladryl, Sunsilk Protect and Rejoice products, exposure to all other cosmetic advertisement on television is not related to the product acceptability of the female residents of the U.P.V. Balay Madayaas. There is no relationship between year level of the respondents and their buying behavior except for Sara Lee and Johnson Baby Shampoo products. Except for Caladryl there is no relationship between year level and acceptability of all other products to the female residents of the U.P.V. Balay Madyaas. Chi-square was used to determine the relationship between exposure to cosmetic advertisement and the buying behavior of the respondents; relationship between exposure to cosmetic advertisement and the product acceptability; relationship between year level of the respondents and their buying behavior and relationship between year level of the respondents and their acceptability of the product using a 0.05 as level of significance. It was find out that relationship between exposure to different cosmetic advertisement on television and the use of advertising elements such as commercial model, music, picture, design and eloquent phraseology cannot be determined. The respondents, who like the product are made only to rank the five advertising elements. Chi-square cannot be used to determine the relationship because there will be empty cells, therefore the result for the computed chi-square will be zero. The researchers only describe the number of respondents who like the product because of the advertising elements employed in the advertisement.